The Viral Hemorrhagic Septicemia Virus (VHSV) Markers of Virulence in Rainbow Trout (Oncorhynchus mykiss) - Baillon, Laury; Mérour, Emilie; Cabon, Joëlle; Louboutin, Lénaïg; Vigouroux, Estelle; Alencar, Anna Luiza Farias; Cuenca, Argelia; Blanchard, Yannick; Olesen, Niels Jørgen; Panzarin, Valentina; Morin, Thierry; Brémont, Michel; et al. (Frontiers in Microbiology, 2020)
Viral hemorrhagic septicemia virus (VHSV) is a highly contagious virus leading to high mortality in a large panel of freshwater and marine fish species. VHSV isolates originating from marine fish show low pathogenicity in rainbow trout. The analysis of several nearly complete genome sequences from marine and freshwater isolates displaying varying levels of virulence in rainbow trout suggested that only a limited number of amino acid residues might be involved in regulating the level of virulence. Based on a recent analysis of 55 VHSV strains, which were entirely sequenced and phenotyped in vivo in rainbow trout, several amino acid changes putatively involved in virulence were identified and introduced, alone or in combination, in a highly-virulent VHSV 23-75 genome backbone by reverse genetics. A total of 35 recombinant VHSV variants were recovered and characterized for virulence in trout by bath immersion. Results confirmed the important role of the NV protein (R116S) and highlighted a major contribution of the nucleoprotein N (K46G and A241E) in regulating virulence. Single amino acid changes in these two proteins drastically affect virus pathogenicity in rainbow trout. This is particularly intriguing for the N variant (K46G) which is unable to establish an active infection in the fins of infected trout, the main portal of entry of VHSV in this species, allowing further spread in its host. In addition, salmonid cell lines were selected to assess the kinetics of replication and cytopathic effect of recombinant VHSV and discriminate virulent and avirulent variants. In conclusion, three major virulence markers were identified in the NV and N proteins. These markers explain the 92.7% of the phenotypes related to 55 VHSV strains included in the present study and herein used for the backwards validation of virulence markers. The identification of VHSV specific virulence markers in this species is of importance both to predict the in vivo phenotype of viral isolates with targeted diagnostic tests and to improve prophylactic methods such as the development of safer live-attenuated vaccines.